Photosynthesis dynamics and regulation sensed in the frequency domain - Nedbal, Ladislav; Lazár, Dušan (Plant physiology, 2021)
Foundations of photosynthesis research have been established mainly by studying the response of plants to changing light, typically to sudden exposure to a constant light intensity after dark acclimation or light flashes. This approach remains valid and powerful, but can be limited by requiring dark acclimation before time-domain measurements and often assumes that rate constants determining the photosynthetic response do not change between dark and light acclimation. We show that these limits can be overcome by measuring plant responses to sinusoidally modulated light of varying frequency. By its nature, such frequency-domain characterization is performed in light-acclimated plants with no need for prior dark acclimation. Amplitudes, phase shifts, and upper harmonic modulation extracted from the data for a wide range of frequencies can target different kinetic domains and regulatory feedbacks. The occurrence of upper harmonic modulation reflects nonlinear phenomena, including photosynthetic regulation. To support these claims, we measured chlorophyll fluorescence emission of the green alga Chlorella sorokiniana in light that was sinusoidally modulated in the frequency range 1000-0.001 Hz. Based on these experimental data and numerical as well as analytical mathematical models, we propose that frequency-domain measurements can become a versatile tool in plant sensing.
Keywords: Photosynthesis; světlo; biosenzitivní techniky; Biosensing Techniques; Chlorella; Light; fotosyntéza